Microwave Assisted Hydrodistillation Essential Oil from Lime Peel Waste as Aromatherapy Candles - Mustam, Mariaulfa; Azis, Hijrah Amaliah; Ramdani, Nurfika; Zalzabila, Nurafdaliana (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Flavonoids belong to the extensive group of polyphenol compounds. They can function as antioxidants and antibacterials by denaturing bacterial cell proteins and damaging bacterial cells. One source of essential oils is lime peel, which is often discarded and goes unused. The distillation method utilizes microwaves, offering an alternative to conventional distillation techniques and resulting in enhanced effectiveness and efficiency. The Microwave Assisted Hydrodistillation (MAHD) method proves to be more energy-efficient, environmentally friendly, rapid, safe, and cost-effective. This study aims to assess the impact of the MAHD method on the quantity and quality of essential oils extracted from lime peels. Laboratory tests are conducted in accordance with Indonesian national standards. The overarching objective is to establish a process that transforms discarded lime peels into aromatherapy candles, contributing to respiratory health. The MAHD method is employed with a sample mass to distilled water solvent ratio of 1:1. The resulting essential oil undergoes analysis using the GC-MS method. According to the GC-MS test results, the compound with the highest percentage area is limonene at 98%. This is followed by trans-caryophyllene at 99% with a retention time of 12.422, and beta-selinene at 99% with a retention time of 13.191.